2012
DOI: 10.1093/nar/gks989
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of mRNA features affecting translation initiation and reinitiation

Abstract: Regulation of gene expression at the level of translation accounts for up to three orders of magnitude in its efficiency. We systematically compared the impact of several mRNA features on translation initiation at the first gene in an operon with those for the second gene. Experiments were done in a system with internal control based on dual cerulean and red (CER/RFP) fluorescent proteins. We demonstrated significant differences in the efficiency of Shine Dalgarno sequences acting at the leading gene and at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
136
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(151 citation statements)
references
References 41 publications
12
136
1
2
Order By: Relevance
“…Bandmann et al developed a mutation library of TrpL-fused eGFP proteins mutated at the first eight AAs and then studied the influence of different kinds of start codons on translation initiation rate [20]. They found that ATG was the best start codon, consistent with another observation that also surprisingly found a high translation initiation rate for the less frequent GTG codon [47]. The integrated nature of these features makes it difficult to perform truly isolated studies of any one of these single variables, but not impossible.…”
Section: Mrna Propertiesmentioning
confidence: 72%
“…Bandmann et al developed a mutation library of TrpL-fused eGFP proteins mutated at the first eight AAs and then studied the influence of different kinds of start codons on translation initiation rate [20]. They found that ATG was the best start codon, consistent with another observation that also surprisingly found a high translation initiation rate for the less frequent GTG codon [47]. The integrated nature of these features makes it difficult to perform truly isolated studies of any one of these single variables, but not impossible.…”
Section: Mrna Propertiesmentioning
confidence: 72%
“…Adenine-rich regions have been shown to enhance expression by increasing the rate and amount of ternary complex formation during initiation (34), likely due to ribosomal protein S1's high affinity for polypyrimidines (43,44). S1-mediated initiation (45,46) occurs in the absence of an SD sequence; therefore, it is possible that S1 also plays a role in ptrB regulation.…”
Section: Discussionmentioning
confidence: 99%
“…4a). Based on a recent report that described the effect of upstream secondary structure within the 5′UTR on translation efficiency [27], we proposed that the aptamer domain of the theophylline riboswitch naturally forming a stem-loop upstream of the SD sequence after transcription augments the accessibility of the ribosome to the SD, eventually producing higher levels of GFP. These results are consistent with previously reported data in which the induced expression levels altered after combining different promoters with the same riboswitch [22, 23].…”
Section: Discussionmentioning
confidence: 99%